Stock price reaction to layoff announcements in Finland: Inter-industry differences - Haapsaari, Henna (My University, 2013)
The purpose of this study is to find out whether a permanent layoff announcement given in the Finnish stock market cause a stock price reaction. More importantly this study aims to research whether the stock price reaction is different across industries. The cho-sen industries - technology, manufacturing, and consumption goods and services - cover three quarters of all the companies listed in the Nasdaq OMX Helsinki Stock Exchange when measured by daily trading volume. Additionally, the differences in abnormal re-turns between business cycles are researched. The data consists of 257 permanent layoff announcements given by 66 companies oper-ating in one of the three industries under observation. Share prices' development was observed during investigation period of 2006–2011. An event study methodology is used to investigate the share price reactions caused by permanent layoffs. Abnormal re-turns are examined for 11 days - four days before the announcement day and six days after it. Permanent layoff announcements do not cause statistically significant stock price reac-tions when the whole sample is considered. Inter-industry differences do exist in the Finnish market. When studying industries separately, the technology portfolio was the only industry that did not react to layoff announcements. The differences in abnormal returns between service-oriented companies and manufacturing companies were also examined and the results showed that service-oriented companies face slightly more negative reaction than manufacturing companies. Different economical situations did affect investors' reactions to layoff announcements. Layoffs given during downturn pe-riods did cause a more negative stock price reaction compared to ones given during up-turn periods.
Keywords: Permanent layoff announcements; market reaction; inter-industry dif-ferences; event study methodology; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|